Anti-freezing, conductive and shape memory ionic glycerol-hydrogels with synchronous sensing and actuating properties for soft robotics. Issue 30 (18th July 2022) - Guo, Meiling; Yang, Xi; Yan, Jiao; An, Zhaojun; Wang, Li; Wu, Yuanpeng; Zhao, Chunxia; Xiang, Dong; Li, Hui; Li, Zhenyu; Zhou, Hongwei
Abstract : Poly(vinyl alcohol)/carboxymethyl cellulose/polyacrylamide/functionalized boron nitride nanosheets ionic glycerol-hydrogels exhibit integrated anti-freezing properties, conductivity and shape memory ability as flexible sensors and actuators. Abstract : Soft devices based on hydrogels are attracting increasing attention, but it is still a challenge to prepare hydrogels with remarkable strength, strain sensing sensitivity, anti-freezing properties, synchronous sensing and actuating properties, simultaneously. Herein, poly(vinyl alcohol)/carboxymethyl cellulose/polyacrylamide ionic glycerol-hydrogels with poly(2-(methacryloyloxy)ethyltrimethylammonium chloride) functionalized boron nitride nanosheets (BNNS-PDMC) as a nano-reinforcing ingredient are developed through the synergistic effect of hydrogen bonding and ionic hydration interaction. The ionic glycerol-hydrogel presents superior freezing tolerance (−70 °C), outstanding tensile strength (1.23 MPa), and high strain sensing sensitivity (gauge factor of 2.6). The sensors based on the ionic glycerol-hydrogel achieve effective detection and discrimination of Morse codes and comprehensive human movements by wireless connection. The ionic glycerol-hydrogel can also be used as a sensor array to obtain visualized stress distribution information. Furthermore, intelligent actuators are also fabricated utilizing the ionic glycerol-hydrogel to detect the deformation of the actuators and output specific electric information. This work inspires a universal route for preparing versatile hydrogels and promises the potential application in smart health care, soft robotics, and human–machine interfaces.